PENGEMBANGAN MEDIA MONOPOLI PADA PEMBELAJARAN IPAS DI KELAS V SD/MI - Husna, Nadiatul; Mawardi; Ridhwan M Daud; Syahidan Nurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop monopoly-based learning media for Natural and Social Sciences (IPAS) in fifth-grade elementary school. The Research and Development (R&D) method followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Subjects included teacher and 24 fifth-grade students at SDN Labuy, Aceh Besar. Data were collected via expert validation sheets and response questionnaires. Results indicated high feasibility, with 100% from media experts and 98.7% from material experts. Teacher (100%) and student (98%) responses confirmed the media's practicality. In conclusion, the developed monopoly media significantly enhances students' motivation and interest in learning IPAS topics.